Adjusting Group Communication in Dense Internet of Things Networks with Heterogeneous Energy Sources - Mota, Renato; Riker, André; Rosário, Denis (Anais do Simpósio Brasileiro de Computação Ubíqua e Pervasiva (SBCUP); 2019: Anais do XI Simpósio Brasileiro de Computação Ubíqua e PervasivaDO - 10.5753/sbcup.2019.6594, 2019)
Internet-of-Things (IoT) environments will have a large number of nodes organized into groups to collect and to disseminate data. In this sense, one of the main challenges in IoT environments is to dynamically manage communication characteristics of IoT devices to decrease congestion, traffic collisions, and excessive data collection, as well as to balance the use of energy resources. In this paper, we introduce an energy-efficient and reliable Self Adjusting group communication of dense IoT Network, called SADIN. It configures the communication settings to ensure a dynamic control of IoT devices considering a comprehensive set of aspects, i.e., traffic loss, event relevance, amount of nodes with renewable batteries, and the number of observers. Specifically, SADIN changes the communication interval, the number of data producers, the reliability level of the network. Extensive evaluation results show that SADIN improves system performance in terms of message loss, energy consumption, and reliability compared to state-of-the-art protocol.